2002
DOI: 10.1542/peds.110.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding and Blood Cholesterol: A Study in Adolescents and a Systematic Review

Abstract: Breastfeeding is associated with increased mean TC and LDL levels in infancy but lower levels in adulthood/adult life. These results suggest that breastfeeding may have long-term benefits for cardiovascular health and may have implications for the content of formula feed milks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
210
2
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(236 citation statements)
references
References 72 publications
12
210
2
12
Order By: Relevance
“…Another possibility is that serum cholesterol levels are not affected by total SAFA intake, but are specifically affected by palmitic and myristic acids (Samuelson et al, 2001). As breastfeeding compared to formula is associated with higher TC levels in infancy, but not lasting after infancy or early childhood, (Å keson Karlsland et al, 1999;Owen et al, 2002) we were surprised by the comparatively low TC levels in our study group and the small change from 6 to 12 months. The number of infants, breastfed at 6 months was close to official national statistics of 76% (The National board of Health and Welfare, 1999).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Another possibility is that serum cholesterol levels are not affected by total SAFA intake, but are specifically affected by palmitic and myristic acids (Samuelson et al, 2001). As breastfeeding compared to formula is associated with higher TC levels in infancy, but not lasting after infancy or early childhood, (Å keson Karlsland et al, 1999;Owen et al, 2002) we were surprised by the comparatively low TC levels in our study group and the small change from 6 to 12 months. The number of infants, breastfed at 6 months was close to official national statistics of 76% (The National board of Health and Welfare, 1999).…”
Section: Discussionmentioning
confidence: 60%
“…Growth rate and nutrition early in life have impact on these diseases later in life, although the associations between obesity, cardiovascular disease (CVD) and serum lipids are complex (Bergström et al, 1995;Berenson et al, 1998;Owen et al, 2002;Thorsdottir et al, 2003). The Bogalusa heart study (Berenson et al, 1998) showed that known risk factors for CVD are present already during childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2005; Owen et al . 2002) for children later in life and reduced risk of cancers (Awatef et al . 2010; Jordan et al .…”
Section: Discussionmentioning
confidence: 99%
“…08)) after adjusting for current age, gender and growth in the previous period (C Corvalan, R Uauy, AD Stein, J Kain and R Martorell, unpublished results). The possibility that early diet conditions the total cholesterol-HDL-cholesterol relationship should be contemplated, although the direction of the associations may be reversed in the long term (79,91) . The authors are presently conducting a follow-up of the cohort to establish these associations at 7 years of age.…”
Section: Effect Of Mode Of Feeding On Growth Obesity and Cvd Riskmentioning
confidence: 99%